2020
DOI: 10.2217/bmm-2020-0069
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Oct4 in Colorectal Cancer: Analysis Using Immunohistochemistry and Bioinformatics Validation

Abstract: Aim: This study was first performed to investigate the role of octamer-binding transcription factor 4 (OCT4) in colorectal cancer (CRC). Methods: The electronic databases were searched for the eligible studies. Odds ratios and hazard ratios were calculated. Functional analysis of OCT4 was examined. Results: Eight studies with 1480 CRC cases were identified. OCT4 expression was correlated with advanced clinical stage, tumor grade, lymph node metastasis, lymphatic invasion, and distal metastasis. OCT4 was an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Several research groups have published results that emphasize the role of OCT4 in the aggressive behavior of CRC and its contribution to forming liver metastasis in CRC, especially OCT4 in the high-expression group, which is consistent with our results ( 66 68 ). Furthermore, OCT4 expression was denoted as an independent prognostic biomarker for predicting worse disease-specific survival and overall survival in CRC ( 69 ). On the other hand, the expression of all OCT4 isoforms in both primary and metastatic samples than in control samples was significantly downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Several research groups have published results that emphasize the role of OCT4 in the aggressive behavior of CRC and its contribution to forming liver metastasis in CRC, especially OCT4 in the high-expression group, which is consistent with our results ( 66 68 ). Furthermore, OCT4 expression was denoted as an independent prognostic biomarker for predicting worse disease-specific survival and overall survival in CRC ( 69 ). On the other hand, the expression of all OCT4 isoforms in both primary and metastatic samples than in control samples was significantly downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 20 ] claimed that the positive expression of Otc4A could be a warning sign for distant recurrence and poor prognosis of rectal cancer in patients undergoing chemoradiotherapy before surgery. Studies have shown that Otc4A protein overexpression plays a role in the development of CRC in the development of colon cancer, and Otc4A is a key transcription factor for maintaining the survival of colon cancer tumor transcription factor critical for the survival of stem cell-like cells [ 21 ]. NF- κ B falls into the category of a nuclear factor that binds to the gene regulatory region encoded by the immunoglobulin k light chain of activated B cells, and the abnormal activation of NF- κ B could enhance cancer cell proliferation by binding to the cyclin D1 promoter [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…OCT4 was reported to be remarkably high expressed in lung adenocarcinoma [19], colorectal cancer [20], cervical cancer [21], ovarian cancer [22], and so on. Our nding indicated that OCT4 could activate angiogenesis and promote ovarian cancer metastasis by regulating LRPPRC/ VEGFR2 axis.…”
Section: Discussionmentioning
confidence: 99%